On determining the nature of Liangzhu 良渚 symbols. (June 2019) - Zhang, Chunfeng
This paper takes five aspects of the symbols of the Liangzhu culture as its subject of study: the quantity of Liangzhu symbols, the ability of these symbols to express meaning and make differentiation, the nature of their conventional usage, the principles of their configuration, and the possibility that Liangzhu symbols represented spoken language. This paper argues that these five aspects show that Liangzhu symbols were a complex system and some of the symbols were already a written language.